An updated review on pharmacological properties of neferine—A bisbenzylisoquinoline alkaloid from Nelumbo nucifera. Issue 12 (14th November 2021) - Bharathi Priya, Lohanathan; Huang, Chih‐Yang; Hu, Rouh‐Mei; Balasubramanian, Balamuralikrishnan; Baskaran, Rathinasamy
Abstract: Phytochemicals have recently received a lot of recognition for their pharmacological activities such as anticancer, chemopreventive, and cardioprotective properties. In traditional Indian and Chinese medicine, parts of lotus ( Nelumbo nucifera ) such as lotus seeds, fruits, stamens, and leaves are used for treating various diseases. Neferine is a bisbenzylisoquinoline alkaloid, a major component from the seed embryos of N. nucifera . Neferine is effective in the treatment of high fevers and hyposomnia, as well as arrhythmia, platelet aggregation, occlusion, and obesity. Neferine has been found to have a variety of therapeutic effects such as anti‐inflammatory, anti‐oxidant, anti‐hypertensive, anti‐arrhythmic, anti‐platelet, anti‐thrombotic, anti‐amnesic, and negative inotropic. Neferine also exhibited anti‐anxiety effects, anti‐cancerous, and chemosensitize to other anticancer drugs like doxorubicin, cisplatin, and taxol. Induction of apoptosis, autophagy, and cell cycle arrest are the key pathways that underlying the anticancer activity of neferine. Therefore, the present review summarizes the neferine biosynthesis, pharmacokinetics, and its effects in myocardium, cancer, chemosensitizing to cancer drug, central nervous system, diabetes, inflammation, and kidney diseases. Practical applications: Natural phytochemical is gaining medicinal importance for a variety of diseases like including cancer, neurodegenerative disorder, diabetes, and inflammation. Alkaloids and flavonoids, which are abundantly present in Nelumbo nucifera have many therapeutic applications. Neferine, a bisbenzylisoquinoline alkaloid from N . nucifera has many pharmacological properties. This present review was an attempt to compile an updated pharmacological action of neferine in different disease models in vitro and in vivo, as well as to summarize all the collective evidence on the therapeutic potential of neferine. Abstract : Natural phytochemical is gaining medicinal importance for a various diseases like cancer, neurodegenerative disorder, diabetes, and inflammation. Alkaloids and flavonoids, which are abundantly present in Nelumbo nucifera have many therapeutic applications. Neferine, a bisbenzylisoquinoline alkaloid form N . nucifera has many pharmacological properties. This present review was an attempt to compile an updated pharmacological action of neferine in different disease models in vitro and in vivo, as well as to summarize all the collective evidence on therapeutic potential of neferine.